Problematizing Contrastive Linguistics: The Connection Between Interlanguage and Error Analysis ("Conference on Universal Science Research 2023", 2023)
This paper challenges contrastive linguistics by highlighting the relationship between interlanguage and error analysis. For data collection and analysis, a quantitative approach was used. To compare and contrast linguistic and socio-cultural data between the shona and the english languages, the researchers used the techniques of contrastive analysis. Although the subject verb agreement between the two languages resembles each other, there are also similarities in that the shona language is implicit in addressing the subject's gender, while the english language is explicit in identifying the subject's gender by the use of explicit pronouns. The findings show that the difficulties in language acquisition are caused by differences between the new language and learners first language. In addition, the two languages studied in this report have distinct typological features. In the study, contrastive analysis methods are suggested for language teaching and learning.